The creative art program for the bright pupils in the elementary school - Parayno, Harlika B. 1939- (College of Education, University of the Philippines Diliman, 1967)
The aim of the study was to determine the features that a good creative art program should have to meet the educational and psychological needs of bright Filipino pupils in elementary schools. Pure library research was conducted in gathering the data. The study maintained that the whole art program should take into consideration the inherent qualities of children and to take the students as children with special endowments in the academic field. It must also be considered that children express themselves differently from adults. Hence these factors were recognized in the objectives, the subject matter, the art materials used, the approaches of the teacher, the proposed activities for the children, and the evaluation of the program in terms of teaching-learning process that were incorporated in the study.